ChemInform Abstract: Simple, but Challenging: Recent Developments in the Asymmetric Synthesis of Spiroketals. Issue 6 (20th February 2013) - Wilsdorf, Michael; Reissig, Hans‐Ulrich
Abstract Review: 21 refs.